INCLUSIVE ISLAMIC ECONOMIC POLICIES IN MUSLIM AND NON-MUSLIM COUNTRIES - Yeti Rohayati (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2023)
The development of Islamic economics has gained increasing global attention, extending beyond Muslim-majority countries to non-Muslim countries seeking sustainable and inclusive economic alternatives. This study aims to analyze the implementation of inclusive Islamic economic policies in Indonesia and Japan, identify the factors supporting and constraining their development, and examine the influence of religious, cultural, and governance backgrounds on policy formulation. The research employs a normative legal method with a comparative approach. Data were collected from secondary legal materials, including legislation, policy documents, institutional reports, and scholarly literature related to Islamic economics in both countries. The analysis focuses on legal frameworks, policy actors, social contexts, implementation mechanisms, and institutional challenges. The findings show that Indonesia integrates Islamic economic principles through a comprehensive regulatory framework supported by government institutions, Islamic financial authorities, and religious organizations. In contrast, Japan adopts a pragmatic and market-oriented approach by facilitating halal industries, tourism services, and international economic cooperation without formally incorporating Islamic law into its legal system. Despite facing different challenges, both countries have demonstrated significant efforts to promote an inclusive Islamic economic ecosystem. The novelty of this research lies in its comparative examination of Islamic economic policies in a Muslim-majority country and a non-Muslim country. The study demonstrates that the successful development of Islamic economics depends not on religious demographics alone but on policy adaptability, institutional support, and stakeholder collaboration, highlighting the universal and flexible character of Islamic economic principles across diverse socio-political contexts.